Pre-equilibrium and Equilibrium Energy Emission Spectrum of Nucleons and Light Nuclei Induce Nuclear Reactions on 63Cu Nuclei - Jasim, Mahdi Hadi; Idrees, Maha Taha (Iraqi Journal of Science, 2022)
The differential cross sections of the pre - equilibrium stage are calculated at different energies using the Kalbach Systematic approach in Exciton model with Feshbach, Kerman and Koonin (FKK) statistical theory of Multistep Compound and direct reactions. In this work, the emission rate of light nuclei with emission energy in the centre of mass system in the isospin mixed case is considered in calculations to predict the cross-sections at the pre-equilibrium and equilibrium stages. The nucleons and light nuclei (2D and 3T) have been used as a projectile at the target 63Cu nuclei and at different incident energies (4MeV, 14 MeV and 14.8MeV). The comparisons between the present calculated results with other, theoretical and experimental works, show an acceptable agreement for certain emission energies for the reactions 63Cu (n, n)63Cu , 63Cu (p, n) 63Zn, 63Cu (p, D) 62Cu , 63Cu (p, p) 63Cu and 63Cu (p, 4He)60Ni.